Two chromatographic schemes for protein purification involving the biotin/avidin interaction under native conditions - Raducanu, Vlad-Stefan; Tehseen, Muhammad; Shirbini, Afnan; Raducanu, Daniela-Violeta; Hamdan, Samir M. (Journal of Chromatography A, 2020)
•Protein purification under native conditions employing the biotin/avidin interaction.•Single expression vector for BirA and AviTag-tagged proteins.•Efficient in vivo biotinylation using BirA enzyme.•An optimized release system from the biotin/avidin interaction.•Efficient coupling of a biotin-tagged bait protein to avidin resin.•Usage of bait protein coupled-Agarose for affinity chromatography. The strength of the biotin/avidin interaction makes it an ideal tool for the purification of biotin-labeled proteins via avidin-coupled resin with high specificity and selectivity. Nevertheless, this tight binding comes at an extra cost of performing the elution step under denaturing conditions. Weakening the biotin/avidin interaction improves the elution conditions, but only to mild or harsh denaturing buffers with the drawback of reducing the specificity and selectivity of this interaction. Here, we present two chromatographic protein purification schemes that are well-suited for application under native conditions thus preserving the strength of the biotin/avidin interaction. In the first scheme, we introduce a biotin-labeled SUMO-tag to each of human flap endonuclease 1 and Escherichia coli replication termination protein Tus, and elute both proteins by performing on-resin cleavage using SUMO protease. In the second scheme, we immobilize biotin-labeled human proliferating cell nuclear antigen (PCNA) on the avidin-coupled resin and use the resulting resin as a tag-free affinity method to purify the PCNA-binding protein human DNA Ligase 1. Furthermore, we streamlined the protein biotinylation protocol by constructing a single plasmid expression system that ensures high level of expression and solubility for each of the target protein bearing the biotin-tag and the enzyme responsible for the in vivo biotinylation reaction. Both chromatographic schemes resulted in a high yield of pure proteins in their native form.